Pelatihan Kewirausahaan Potong Rambut sebagai Alternatif Peningkatan Kemandirian Pesantren dan Santri - Wibisono, Bambang; Haryono, Akhmad; Agustini, Aisa Tri (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Islamic boarding schools are alternative education places for rural communities that contribute greatly to the development of human resources. However, graduates from the Raudlatul Mubtadi-in Islamic Boarding School, in Pancakarya Village, Ajung District have not been able to be independent. Therefore, entrepreneurship development training activities are needed for students. One of them is haircut entrepreneurship training. In this hut there are already some students who can cut their hair with talent. However, they still use makeshift tools, have not been able to cut with modern tools (clipers), and have not mastered various styles of cutting hair. Using a participatory approach, training and mentoring, in this PKM training and assistance in haircuts using modern haircuts is carried out, and enrichment of haircut models according to community needs, and entrepreneurial management training. This program can develop the potential of students in haircut skills, it can be used to increase the independence of students and pesantren. With these skills, students can at least transmit their skills to other students, and can open a hair cutting business. This training has succeeded in attracting the interest of the students and can be used as an alternative for developing the skills and independence of the students.